Pride and prejudice. - Austen, Jane, 1775-1817 (Norton critical edition., 2016)
Jane Austen's classic comedy of manners is one of the most enduring love stories in English literature In a remote Hertfordshire village in the early nineteenth century, Mr. and Mrs. Bennet have a problem. Or rather, five vivacious, headstrong problems: Jane, Elizabeth, Mary, Catherine, and Lydia. Mr. Bennet loves his daughters dearly, but spends more time with his nose buried in a book than planning for their futures. Since her husband's property can only pass to a male heir, Mrs. Bennet insists that the girls find rich husbands. But her daughters would rather fall in love than listen to their mother's advice. Jane, the eldest and most beautiful, attracts the attentions of a young gentleman named Charles Bingley, but his good friend Mr. Darcy disapproves of the match. Elizabeth, always eager to defend her sweet-natured sister, detests the prideful Mr. Darcy, even after he asks for her hand in marriage. But when a chance encounter reunites the combative couple, Elizabeth realizes that her prejudices have been standing in the way of her heart's true desire. A razor-sharp satire of English country life and a stirring tribute to the power of romance to overcome the longest of odds, Pride and Prejudice is Jane Austen's masterwork and one of the finest novels ever written. This ebook has been professionally proofread to ensure accuracy and readability on all devices.